Prediction of Cross-Link Density of Prevulcanized Latex Using InGaAs NIR Spectroscopy - Dachapan, Suntaree; Saengprachatanarug, Khwantri; Phuphaphud, Arthit; Sirisomboon, Panmanas; Lim, Chin Hock; Posom, Jetsada (My University, 2026)
Cross-link density plays a critical role in determining the mechanical strength, elasticity, and long-term performance of prevulcanized (PV) latex products. This study aimed to evaluate the feasibility of near-infrared (NIR) spectroscopy for predicting cross-link density in PV latex using InGaAs-based instruments. Two spectrometers operating in the 960–1700 nm range were investigated: a noncontact MicroNIR and a contact AvaSpec system. Partial least-squares regression (PLSR) models were developed using two data sets. Data set I contained only NIR spectra, whereas Data set II combined spectra with industrial process variables, including holding time and latex grade. Cross-link density was referenced using the Prevulcanizate Relaxed Modulus (PRM, 100% and 300% elongation) and Toluene Swelling Index (TSI, 3 and 6 h) methods. Models based solely on Data set I showed limited predictive performance, while Data set II yielded markedly improved accuracy, highlighting the importance of integrating process information. The TSI-based models consistently surpassed PRM, with TSI-3 h identified as the most reliable reference. Using MicroNIR, the best TSI-3 h and TSI-6 h models achieved SEP values of 5.64 × 104 and 5.96 × 104 N·m– 2 and R2 values of 0.96 and 0.95, respectively. Comparable performance between contact and noncontact instruments further confirmed the practicality of noncontact NIR measurement. This work demonstrates, for the first time, that combining InGaAs NIR spectroscopy with process variables enables accurate, rapid, and nondestructive forecasting of TSI-based cross-link density for PV latex manufacturing.